2019
DOI: 10.1111/tbj.13199
|View full text |Cite
|
Sign up to set email alerts
|

Safety of eribulin as third-line chemotherapy in HER2-negative, advanced breast cancer pre-treated with taxanes and anthracycline: OnSITE study

Abstract: Eribulin is active and safe in heavily pre‐treated metastatic breast cancer patients. Few safety data have been published in third line. We aimed to report the specific safety profile on third line beyond taxanes and anthracyclines in advanced breast cancer (ABC). A multicenter phase II, prospective study was conducted in anthracyclines and taxanes pre‐treated HER2‐negative ABC, programmed to receive eribulin as third‐line chemotherapy. Adverse events (AEs) were assessed and classified according to CTCAE. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Symonds et al [71] revealed that a decrease in CTC numbers from baseline to the first assessment after employing nab-paclitaxel and bevacizumab therapy followed by maintenance therapy with bevacizumab and erlotinib by metastatic TNBC patients correlated with prolonged PFS and OS. Similar results were noticed in the OnSITE study analyzing the CTC number before and after the second cycle of treatment of the HER2-negative advanced BC patients pre-treated with anthracyclines and taxanes, who received eribulin as third-line chemotherapy show similar results [72]. Liang et al [73] analyzed the number of CTCs as one of the efficacy parameters for the comparison of three therapy strategies for tumor cryoablation with natural killer (NK) cells therapy (I, cryoablation; II, cryoablation + NK cell therapy; III, NK cell therapy-Herceptin) and Herceptin for patients with HER2-overexpressing recurrent BC.…”
Section: Ctc Enumeration-breast Cancersupporting
confidence: 84%
See 1 more Smart Citation
“…Symonds et al [71] revealed that a decrease in CTC numbers from baseline to the first assessment after employing nab-paclitaxel and bevacizumab therapy followed by maintenance therapy with bevacizumab and erlotinib by metastatic TNBC patients correlated with prolonged PFS and OS. Similar results were noticed in the OnSITE study analyzing the CTC number before and after the second cycle of treatment of the HER2-negative advanced BC patients pre-treated with anthracyclines and taxanes, who received eribulin as third-line chemotherapy show similar results [72]. Liang et al [73] analyzed the number of CTCs as one of the efficacy parameters for the comparison of three therapy strategies for tumor cryoablation with natural killer (NK) cells therapy (I, cryoablation; II, cryoablation + NK cell therapy; III, NK cell therapy-Herceptin) and Herceptin for patients with HER2-overexpressing recurrent BC.…”
Section: Ctc Enumeration-breast Cancersupporting
confidence: 84%
“…For a long time, the main applications of CTCs in clinical trials were based only on enumeration. Many investigators suggest that enumeration could be an independent prognostic factor of DFS or OS, or at least in combination with other agents [21,26,28,62,69,72,77]. The statement of the PCWG published by Scher et al [8] confirmed the importance of CTC enumeration.…”
Section: Perspectives Of Real-time Monitoringmentioning
confidence: 99%
“…A recent multicenter phase II study, the OnSITE, evaluated eribulin as third-line therapy in anthracyclines and taxanes pretreated patients, confirming the usual safety profile. Median PFS and OS were 4 and 13.6 months, and median OS was associated with baseline lower (<5) circulating tumor cells 29. A phase II single arm study of eribulin from first to third-line in advanced disease was conducted in Japan, enrolling 47 patients, with an overall RR of 17%, a median PFS of 4.9 months, and a median OS of 17.4 months.…”
Section: Eribulin Mechanism Of Action and Clinical Studies In Advancementioning
confidence: 99%
“…15,16,27 We showed that our combination therapy led to stable disease in 60% of the patients and was associated with a median PFS time of 3.95 months, which was comparable with or F I G U R E 1 A waterfall plot shows best tumor responses in 15 patients with metastatic ASS1 deficient solid tumors treated with ADI-PEG20 and liposomal doxorubicin F I G U R E 2 Kaplan-Meier curves of progression survival (PFS, blue, 3.95 months, 95% confidence interval, 0.86-7.04) and overall survival (OS, red, not evaluable with 11 patients censored) in 15 patients with metastatic ASS1 deficient solid tumors treated with ADI-PEG20 and liposomal doxorubicin better than those for other regimens as fourth-line or later treatment of HER2-negative breast cancer. [31][32][33] The pharmacodynamic activity of ADI-PEG 20 was evidenced by rapid and durable depletion of arginine from peripheral blood. Of note, arginine reduction and citrulline elevation induced by ADI-PEG 20 combined with PLD were more prolonged than those observed previously with ADI-PEG 20 alone or combined with other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 27 We showed that our combination therapy led to stable disease in 60% of the patients and was associated with a median PFS time of 3.95 months, which was comparable with or better than those for other regimens as fourth‐line or later treatment of HER2‐negative breast cancer. 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%